Huckepack transport u zaštiti čovjekovog okološa i sigurnosti prometa - Marković, Ivo (Promet - Traffic&Transportation, 2012)
Piggy-back transport has been up to this point of time the most efficient segment of freight transport by means of modern technologies combining rail and road aspects. This modern transport mode as compared to traditional transport offers a variety of advantages in the shape of: economical consumption of petroleum products, higher rail and road fleet utilization coefficient, longer road vehicle(s) operation life, reduced wear of carriageways, higher-quality and safer transportation, reduced transportation costs, environmental concerns, etc. In our country in 1981 and 1982 respectively a piggy-back train was 6perating on the Jesenice- Ljubljana and Zagreb-Belgrade-Gevgelia routes to be cancelled subsequently: such a train is presently operating only on the Jesenice-Ljubljana- Koper route. In the light of the above listed advantages it will absolutely be necessary to re-introduce this train on the one-time routes, as well as on the Zagreb-Rijeka and ZagrebSplit and Zagreb-Osijek- Vinkovci routes. Measures on the prevention of adverse environmental effects of traffic and legislative, management, engineering and technological, educational and other effects as dealt with in this paper) should necessarily be updated, modernized and intensified in their implementation. This will yield the expected and aspired-to effects of environmental protection and advanced traffic safety.